The challenges of law against the advance of new technologies in assisted human reproduction: A case of surrogate - Rodríguez-Cadilla Ponce, Roxana (2018)
The so-called Assisted Human Reproduction Techniques (TERAS) constitute a true technological revolution that is being applied to human life and procreation. The so-called “miracles” of modern science have made it possible to solve one of the problems of greatest concern for the human being: infertility. In Peru, there is no specific regulation on these techniques, beyond what is established in Article 7 of the General Health Law; being that the use of TERAS, including the so-called “surrogate belly” are an increasingly frequent reality in our country. The present article raises some reflections on the new challenges that face the right before the new technologies, in the matter of assisted human reproduction; from an amparo process in which the filiation of two minors (twins) procreated through these techniques and with the support of a pregnant-collaborator is discussed. That is to say, a case of “surrogate belly” in the modality of “solidary belly”, whose firm sentence recognizes the motherhood of those who did not bring the ovum, nor carried out the gestation. It is a resolution that declares as a mother, for all its legal and non-legal effects, who had exclusively the will to procreate, proposing a new assumption of affiliation, “affective-social” type, which generates jurisprudence in this matter.